The vapor effect of alcoholic extracts of some plants on adults and larvae of the red flour beetle Tribolium castaneum )Colioptera: Tenebrionidae( in the laboratory (Damascus University Journal of agriculture sciences, 2024)
The study was carried out in the laboratory of pesticides in Plant Production Dept. and Biological Control Studies and Research Center (BCSRC), in the Faculty of agriculture / Damascus University. during 2021-2022 . The study aimed to evaluate the efficacy of ethanol plant extracts obtained from leaves of lavender (Lavandula angustifolia), Chinaberry (Melia azedarach), and Eucalyptus (Eucalyptus camaldulensis) and seed of Cumin (Cuminum cyminum) on adult and larvae of flour beetle red (Tribolium castaneum) in laboratory.The results showed that the LC50 values after 48 hours for red flour beetle adults were 6.38, 7.05, 10.67, and 20.25 μL./L. air, while the LC50 values after 48 hours for red flour beetle larvae were 3.67, 4.68, 5.98, and 17.16. μL./L. air for lavender, cumin, Chinaberry, and eucalyptus, respectively. The results showed that the alcoholic extracts of lavender leaves and cumin seeds were significantly superior to all treatments and in both treatment of evaporation adults and larvae of the red flour beetle. The effectiveness of alcoholic extracts of the tested plants increased with increasing concentration and exposure time.
Keywords: Flour Beetle Red; Plant Extracts; Lavender; Chinaberry; Syria